Clinically granulomatous cheilitis with plasma cells - Somenath Sarkar; Sarmistha Ghosh; Dipayan Sengupta (Wolters Kluwer Medknow Publications, 2016)
Plasma cell cheilitis, also known as plasma cell orificial mucositis is a benign inflammatory condition clinically characterized by erythematous plaque on lips that may be ulcerated. Histopathologically it is characterized by dense plasma cell infiltrates in a band-like pattern in dermis, which corresponds to Zoon's plasma cell balanitis. On the other hand, granulomatous cheilitis, as a part of orofacial granulomatosis, manifests as sudden diffuse or nodular swelling involving lip and cheek. Initial swelling is soft to firm, but with recurrent episodes swelling gradually become firm rubbery in consistency. We hereby report a case of cheilitis in a 52-year-old man with diffuse swelling involving lower lip, which clinically resembles granulomatous cheilitis, but histopathological examination showed diffuse infiltrate of plasma cells predominantly in upper and mid-dermis.